2020
DOI: 10.1148/ryct.2020204002
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Chest CT Findings in Cases from the Cruise Ship “Diamond Princess” with Coronavirus Disease 2019 (COVID-19)

Abstract: This erratum corrects an error in the number of cases in the study. The number of cases decreased from 112 to 104. These eight cases need to be omitted from the study for the following reasons:After submission of the manuscript, three persons withdrew their consent for research on discharge. As per IRB approval documentation of the study, three people need to be omitted from the study. Authors were notified about their withdrawal from the IRB only after online publication.The authors double-counted five cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 0 publications
7
104
0
10
Order By: Relevance
“…In 58 asymptomatic patients with RT-PCR-confirmed COVID-19, Meng et al found chest CT abnormalities in all patients, with no CT remaining normal [ 17 ]. These findings are counterbalanced by the report of 76 asymptomatic patients from the Diamond Princess, where Inui et al found chest CT lesions in 41 of them, with 35 (46%) chest CT remaining normal [ 18 ]. This range of normal examinations is also confirmed by Bandirali et al in 170 chest radiographs in asymptomatic patients, with 70 (41%) remaining normal [ 19 ].…”
Section: Discussionmentioning
confidence: 96%
“…In 58 asymptomatic patients with RT-PCR-confirmed COVID-19, Meng et al found chest CT abnormalities in all patients, with no CT remaining normal [ 17 ]. These findings are counterbalanced by the report of 76 asymptomatic patients from the Diamond Princess, where Inui et al found chest CT lesions in 41 of them, with 35 (46%) chest CT remaining normal [ 18 ]. This range of normal examinations is also confirmed by Bandirali et al in 170 chest radiographs in asymptomatic patients, with 70 (41%) remaining normal [ 19 ].…”
Section: Discussionmentioning
confidence: 96%
“…Chest HRCT plays an important role in the detection of COVID-19 pneumonia, with reported sensitivity ranging from 61% [ 4 ] to 99% in a study performed in a setting with high disease prevalence [ 5 ]. Typical findings include GGO and consolidation, involving multiple lobes of both lungs [ 6 ], as well as OP pattern [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 Although not a study of incidental findings on chest CT, imaging findings in 112 cases of COVID-19-positive patients on board the “Diamond Princess” cruise ship were analyzed. 27 Fifty-four percent of asymptomatic patients who tested positive for COVID-19 had abnormal findings on chest CT. No significant differences in age, gender, or comorbidities were identified in symptomatic versus asymptomatic cases. Asymptomatic patients showed a lower CT severity score and predominant GGO, whereas symptomatic patients showed predominant consolidation.…”
Section: How Should a Radiologist Deal With Incidental Findings Of Comentioning
confidence: 99%